BARRIERS TO ADHERENCE TO EXPANDED PROGRAM ON IMMUNIZATION AMONG PARENTS IN LANAO DEL NORTE, PHILIPPINES - Geraldine Sabate Ridad (Belitung Raya Foundation, Indonesia, 2019)
Background: The Expanded Program on Immunization (EPI) was developed to ensure access of infant and children to recommended vaccines. In the Philippines, nurses are deployed in the community to ensure that children in their assigned units are fully immunized before they reach 1 year old. However, despite the various immunization campaigns, many children still remain unprotected and at-risk to life-threatening vaccine-preventable diseases. Thus, identifying the barriers that have averted parents from adhering to complete and timely immunization is important, most especially to nurses who are the primary program implementers in the community. Objective: This study chiefly aimed to determine the respondents’ perceived barriers along the aspects of Personal, Geographical and Social Barriers, Beliefs and Myths on Immunization, and Knowledge and Awareness on EPI and their relationship to the respondents’ level of adherence to immunization. Methods: Descriptive correlational design was used to explore the perceived barriers to immunization and examine its relationship to the respondents’ level of adherence. A researcher-constructed questionnaire was used after being pilot tested to gather data from 352 random respondents. Results: Using frequency counts, percentages, and weighted arithmetic mean, the results showed that most of the respondents considered only geographical factors as barrier along with social factors. Moreover, it has been found out that respondents lacked knowledge and awareness on the benefits of immunization, the number of vaccines their child needs to receive, site and schedule, side-effects, and contraindications. However, with mean above 2.34 indicated that respondents were informed on the appropriate interventions for side-effects of vaccines, as well as their right to refuse vaccination. The respondents’ over-all level of adherence was moderate. Conclusion: The identified barriers geographical, social, personal, beliefs and myths on immunization and respondents’ level of knowledge and awareness have influenced respondents’ level of adherence to a moderate level only. Based on the results, health care providers, especially nurses, and other concerned program implementers need to consider and address these barriers when formulating or improving strategies to increase immunization compliance. Lastly, more intentional follow-up campaign drives in spreading information about Expanded Program on Immunization using media and other ways is needed.